Risk Factors for Transmission of the SARS-Cov 2 Virus in Health Workers - Saza Fitria; Ede Surya Darmawan; Amelia Rizki Alfriantin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Healthcare workers (HCWs) serve as front liners in the battle against COVID-19. They are often expected to be in constant contact with infected patients, posing higher risk of transmission. To date, literature on risk factors of COVID-19 transmission in HCWs are still limited. Purpose: We conducted this systematic review to identify the risk factors for SARS-CoV-2 virus transmission among HCWs. Methods: We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. Four internet databases were searched using predefined search terms. The keywords used were {“COVID-19” OR “SARS-CoV-2”}, {“transmission” OR “transmission risk”}, and (“healthcare professionals” OR “healthcare workers” OR “healthcare staff”). All English articles which were published from January 2020 to June 2021 involving HCWs in hospitals treating COVID-19 were included into the study. Results: Out of initial 636 studies found using the predefined search terms, 18 studies fulfilled the inclusion criteria and were subsequently analyzed. We found that risk factors for COVID-19 could be divided into 5 categories: use of personal protective equipment (PPE), infection control procedures, unsafe workplace practices, provision of institutional support, and presence of individual risk factors in healthcare workers. Good hospital governance is necessary to establish policies regarding control of COVID-19 infection which will protect the patients and HCWs. Conclusion: Proper use of PPE, compliance to proper infection control procedures, establishment of safe workplace practices, provision of institutional support for prevention measures, and lack of individual risk factors may reduce the transmission risk of SARS-CoV-2 virus among healthcare workers. Further studies are warranted to identify methods for reducing incidence and mortality rate due to COVID-19 at HCWs.